تنمية الوعي الأمني للتلاميذ المعاقين ذهنياً في ضوء رؤية المملكة العربية السعودية 2030 - حلمي عبد الحميد طلبة, منى (حلمي عبد الحميد طلبة,منى.تنمية الوعي الأمني للتلاميذ المعاقين ذهنياً في ضوء رؤية المملكة العربية السعودية 2030. مجلة العلوم النفسية والتربوية. مج 03 ع04. 01/12/2017 . جامعة الوادي [أكتب تاريخ الاطلاع] متاح على الرابط[أنسخ رابط التحميل], 2017)
تتحدد أهداف الدراسة في التعرف على كيفية تنمية الوعي الأمني للتلاميذ المعاقين ذهنياً في ضوء رؤية المملكة العربية السعودية 2030، وذلك من خلال إلقاء الضوء على مفهوم الوعي الأمني، وعوامل تحققه مع المعاقين ذهنياً في البيئة المدرسية، وخصائص البيئة المدرسية الآمنة لهم في ضوء رؤية 2030، والإجراءات التي تتبعها الإدارة لتنمية الوعي الأمني لديهم، وتم عرض بعض الدراسات المرتبطة بموضوع الدراسة، يلي ذلك عرض لمنهجية الدراسة فقد استخدام المنهج الوصفي الذي يعتمد علي جمع البيانات وتحليلها وهو ما يتناسب مع طبيعة الدراسة الحالية، ولتحقيق أهداف الدراسة تم تصميم استبانة تحتوي على(20) عبارة، وقد تم التحقق من صدق الاستبانة بالتحكيم، وحساب ثباتها باستخدام معامل ألفا كرونباخ، وتكونت عينة الدراسة من (40) معلم من معلمي المعاقين ذهنياً بمعهد التربية الفكرية بمحافظة الطائف، وبعد تطبيق الاستبانة تم تحليل البيانات إحصائياً باستخدام المتوسطات الحسابية والانحرافات المعيارية، وخلصت الدراسة إلي ضرورة تنمية الوعي الأمني بين التلاميذ المعاقين ذهنياً في البيئة المدرسية وجعل المدرسة أكثر أمانا للمعاقين ذهنياً ، وقد اختتمت الدراسة إلى مجموعة من التوصيات في هذا الصدد. he objectives of the study are to identify how to develop the security awareness of students with mental disabilities in the light of the vision of Saudi Arabia 2030 by shedding light on the concept of security awareness and factors to achieve with mentally disabled in the school environment, And the characteristics of the school environment safe for them in the light of the vision of 2030, and the procedures followed by the administration to develop their security awareness, and some of the studies related to the subject of the study were presented, followed by a presentation of the methodology of the study has been the use of the descriptive method, which depends on the collection of data and analysis, Which is commensurate with the nature of the current study, o achieve the objectives of the study, a questionnaire was designed containing(20) phrase. The validity of the questionnaire was verified by arbitration and its stability was calculated using the Pearson Correlation Coefficient. The sample of the study consisted of(40) teachers of mentally handicapped teachers at the Institute of Intellectual Education in Taif Governorate. Analyzing data statistically using arithmetic averages and standard deviations, the study concluded that the need to develop the security awareness among students with mental disabilities in the school environment and make the school safer for the mentally disabled. The study concluded with a set of recommendations in this regard.
مقال
Keywords: الوعي الأمني؛ التلاميذ المعاقين ذهنياً ؛ رؤية المملكة العربية السعودية 2030م; Security Awareness; Mentally retarded students; Saudi Arabia's vision 2030.